Synthesis and Biological Evaluation of Some 4-Substituted Quinoxalinones - J. INGALE, SANJAY; PRAKASH B.N. GUPTA, SURYA; UPMANYU, NEERAJ; PANDE, MILIND (Asian Journal of Chemistry, 2010)
A number of quinoxaline-2-ones analogues have been synthesized by condensation of parent compound with different acid chlorides and screened for antibacterial activity against Escherichia coli, Bacillus subtilis, Bacillus cereus and Staphylococcus aureus and antifungal activity against Aspergillus niger and Candida species and analgesic activity. The 4-substituted quinoxalinones were characterized using TLC, IR, 1H NMR analysis.